Abnormal uterine bleeding in VTE patients treated with rivaroxaban compared to vitamin K antagonists. Issue 4 (October 2015) - De Crem, Nico; Peerlinck, Kathelijne; Vanassche, Thomas; Vanheule, Kristine; Debaveye, Barbara; Middeldorp, Saskia; Verhamme, Peter; Peetermans, Marijke
Abstract: Introduction: Rivaroxaban is a convenient oral anticoagulant for patients with venous thromboembolism (VTE). The impact of rivaroxaban and vitamin K antagonists (VKAs) on abnormal uterine bleeding (AUB) in real life has not been previously explored. Materials and methods: We performed a single‐center retrospective study on AUB in female VTE patients of reproductive age who were treated with either rivaroxaban or VKAs. Results: Questionnaire results were available for 52 patients in each treatment group. Approximately two thirds of all women reported AUB after initiation of anticoagulant therapy. Patients using rivaroxaban were more likely to experience prolonged (> 8 days) menstrual bleeding (27 % vs. 8.3%, P = 0.017). Rivaroxaban treatment increased the duration of menstrual bleeding from median 5 (IQR 3.5-6.0) days before start of treatment to 6 (IQR 4.1-8.9) days (P < 0.001). VKA treatment did not lead to significant prolongation of the menstrual period. Patients on rivaroxaban more frequently reported an unscheduled contact with a physician for AUB than women using VKAs (41% vs. 25%, P = 0.096). They also reported increased need for menorrhagia-related medical or surgical intervention (25% vs. 7.7%, P = 0.032) and had more adaptations of anticoagulant therapy (15% vs. 1.9%, P = 0.031). Conclusion: AUB is frequent after initiation of anticoagulant therapy for acute symptomatic VTE. Compared to VKAs, rivaroxaban was associated with prolonged menstrual bleeding and more medical interventions and adaptation of anticoagulant treatment for AUB. These data can guide proactive discussion with patients starting anticoagulant therapy. Highlights: Rivaroxaban offers convenient oral anticoagulation for patients with VTE. Abnormal uterine bleeding (AUB) is frequent during anticoagulant therapy. Treatment with rivaroxaban is associated with prolonged menstrual bleeding vs. VKA. VTE patients on rivaroxaban ( vs. VKA) report more medical interventions for AUB. Strategies to mitigate AUB, e.g. continued oral contraceptive use, need further study.